Analisis Kesiapan Fasilitas dan Personel Unit Aviation Security di Bandar Udara Internasional Adi Soemarmo Boyolali Dalam Rangka Pembukaan Kembali Rute Internasional - Damayanti, Sonia Firsty; Tamara, Amelia Puspa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The recovery of situation due to the spread of the Covid-19 virus, several airports will reopen international routes. Therefore the purpose of this research is to analyze the readiness of the facilities and personnel of the aviation security unit at Adi Soemarmo Boyolali International Airport in the reopening of international route. This research was conducted from 5 December 2022 to 5 January 2023, at Adi Soemarmo Boyolali International Airport. This research used a qualitative method, including data obtained from observations at the Adi Soemarmo Airport terminal, interviews with aviation security personnel, and supporting documentation. The results of this study indicate that the Aviation Security unit at Adi Soemarmo Boyolali International Airport is ready for the reopening of international routes. The facilities owned are certified in accordance with KP 138 of 2018. The number of personnel available is sufficient to carry out their duties and the working hours of personnel are in accordance with Law Number 13 of 2003. The obstacles experienced by personnel are that there are still several facilities that are not yet available and the need for additional personnel aviation security when there is a reopening of international routes. Keywords: Fasilities Aviation Secuity, Personnel Aviation Security, Readiness